1. The problem statement, all variables and given/known data I = Identity matrix Suppose that A^2 = A. Prove that I - 2A = (I - 2A)^-1 2. Relevant equations ahh don't know what to put here 3. The attempt at a solution So I have to prove this thing is it's own identity... interesting.. I - 2A = I - 2A^2 (I - 2A^2)*(I - 2A)^-1 = I Distributive law? Idk honestly this is all I have gotten.. And it's probably not the right direction, just trying to put all the information I know into one line I guess. Any Mathamavericks out there wanna help a noob out?